2023
DOI: 10.3399/bjgpo.2023.0074
|View full text |Cite
|
Sign up to set email alerts
|

Long COVID as a never-ending puzzle: the experience of primary care physicians. A qualitative interview study

Danica Rotar Pavlic,
Alem Maksuti,
Matic Mihevc
et al.

Abstract: BackgroundLong COVID provides a new context in which primary healthcare needs to be reexamined, especially because it has health and social dimensions. The experiences of care for patients with long COVID and primary care physicians’ perceptions are an unexplored area.AimTo explore the experiences of Slovenian primary care physicians in management and treatment of patients with long COVID.Design & settingA qualitative interview study in Slovenian primary care was carried out between November 2021 and April… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Meanwhile, this study’s findings contrast with those of much previous research in the area as they provide a close focus on the perspectives of general practice stakeholders. And while the findings of studies conducted by Jamoulle et al [ 10 ], Rotar Pavlic et al [ 34 ], and Taylor et al [ 35 ] also focused on long COVID in general practice, we believe this study is the first to examine both stakeholder groups simultaneously using a comparative analysis technique. By using the constant comparison method, we were able to highlight previously unpublished points of agreement between GPs and patients regarding long COVID care, as well as differences between the priorities that both groups held.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Meanwhile, this study’s findings contrast with those of much previous research in the area as they provide a close focus on the perspectives of general practice stakeholders. And while the findings of studies conducted by Jamoulle et al [ 10 ], Rotar Pavlic et al [ 34 ], and Taylor et al [ 35 ] also focused on long COVID in general practice, we believe this study is the first to examine both stakeholder groups simultaneously using a comparative analysis technique. By using the constant comparison method, we were able to highlight previously unpublished points of agreement between GPs and patients regarding long COVID care, as well as differences between the priorities that both groups held.…”
Section: Discussionmentioning
confidence: 90%
“…Of the eight qualitative studies found relating to long COVID in general practice and primary care, two simultaneously examined the perspectives of primary care practitioners (not GPs) and patients [ 28 , 33 ]. Other studies examined the views of GPs [ 34 ], general practice patients [ 10 ], patients recruited from the community rather than from primary care or general practice [ 30 ], patients referred to a primary care integrated psychology service [ 24 ], doctors from social media (of which eight were GPs) [ 35 ], and members of the general public recruited via social media [ 20 ]. The largest study sample containing both general practice / primary care practitioner and patient participants involved 198 paricipants (patient n = 126; primary care practitioner n = 72) and employed content analysis of open-ended survey responses rather than in-depth interviews [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an interview study, GPs also reported major challenges in treating patients with long COVID. In particular, the diagnosis of long COVID, the handling of psychosocial problems and the ability to work of affected patients, and the prescription of rehabilitation measures caused great difficulties for GPs due to the lack of uniform guidelines [ 49 ].…”
Section: Discussionmentioning
confidence: 99%